How obstetricians experience stillbirth and perinatal loss: a systematic review and meta-synthesisAJOG Global Reports at a Glance - Frances Cates; Sara Wetzler; Tabitha Wishlade; Mehali Patel; Catherine E. Aiken, MB/BChir, PhD (AJOG Global Reports, 2025)
Objective: Globally, ∼2 million babies are stillborn annually, many in low- and middle-income countries. We aim to understand the experience of obstetricians caring for parents who experience stillbirth and perinatal loss across global settings. Data Sources: : Medline via Ovid, Embase via Ovid, CINAHL via Ebsco, PsychINFO via Ebsco, Scopus, Web of Science Core Collection, and ASSIA via Proquest were searched, database inception-June 2024. Study Eligibility Criteria: Studies with qualitative components describing experiences of obstetricians providing stillbirth care in any global setting. Study Appraisal and Synthesis Methods: The Critical Appraisal Skills Programme checklist for qualitative research was utilized to conduct quality assessment. NVivo software was employed for inductive coding and thematic analysis. Results: Thirteen qualitative studies from both low- and high-resource settings met the inclusion criteria for meta-synthesis. We identified several major themes including the emotional burdens experienced by obstetricians providing stillbirth care, the challenges of patient-provider interactions following adverse outcomes, and a lack of support and resources. Obstetricians across global settings felt devastation, guilt, blame, and a sense of personal responsibility following stillbirth. Obstetricians struggled to navigate the burden of expectation placed on their overall provision of care and tended to question their own professional competence. A subset of obstetricians felt unprepared for the complexity of patient-provider interactions following stillbirth. Conclusions: Obstetricians experienced complex and conflicting emotions, citing high emotional burden from managing stillbirth cases. Obstetricians identified lack of training and support for providing bereavement care across healthcare settings, indicating a gap that should be filled by stillbirth and bereavement care interventions and education in obstetrical training programs across global settings. Infrastructure for bereavement care training and support systems for obstetricians are crucial to improve the quality of stillbirth and perinatal loss care and prevent an exodus of needed providers for women's care worldwide.